Annie and Snowball and the Magical House - Rylant, Cynthia; Stevenson, Sucie (New York : Aladdin, 2010)
Annie takes her rabbit to the home of her new friend, Sarah, to play and enjoys seeing the pretty house full of frilly things, walking in the beautiful garden, and making a tiny garden house for a fairy tea party.
Accelerated Reader AR